Description of Mother's Knowledge of Posyandu and Toddler Visits to Posyandu in Sidoarjo Regency - Aisyatun Nadhilah; Djauharoh Djauharoh (Indonesian Journal of Cultural and Community Development, 2022)
Toddler visits to posyandu are toddlers who come to posyandu to get health services such as weighing, immunization, and others. Based on initial data obtained at the Posyandu of Sumber Terik Village in January-December 2018 from 128 toddlers, it was found that 55 (43%) toddlers regularly came to Posyandu, and as many as 73 (57%) toddlers did not regularly come to Posyandu. The research design used descriptive. The population is 30 mothers in Rt:09 Rw:03 who have toddlers aged 1-5 years. The data obtained were recapitulated and then presented in the frequency table and the cross table was analyzed descriptively without statistical tests. Data collection uses primary data from questionnaire sheets and secondary data from KMS/KIA books. The results showed that most (66.7%) of mothers' knowledge was lacking, most (60%) of under-five visits were not routine, indicating that almost half (33.3%) of respondents had sufficient knowledge. Almost half (40%) visits under five are routine. The conclusion of the study is that the visits of children under five to the posyandu are routinely carried out by mothers who have sufficient knowledge compared to mothers who have less knowledge.